Using TED Talks In English Language Teaching (ELT): Supplemental Resources for English Language Teaching (ELT) - Tira Nur Fitria (Yayasan Literasi Sains Indonesia, 2022)
The objective of this research is to discuss using TED Talks in English Language Teaching (ELT). This research uses the descriptive qualitative method. Based on the findings, it shows that TED Talks can help students learn a variety of skills on English skills such as speaking, listening, and writing skills. In speaking, TED Talks allow the students in listening to a good example of talks/lecturers and to analyze how they are structured and presented. The students can be given the opportunity outside of class to watch selected TED Talks, so these talks are can be analyzed in class and the students are familiar with the language and content. In listening, TED talks are delivered by native English speakers from all over the world which allows the students to see some TED chats about a subject that concerns them, by merely listening to a native English speaker. They can help develop their understanding, vocabulary, and pronunciation skills. In writing, available TED Talks’ transcripts allow the students to read along with the spoken word. This can develop their skills in grammar and vocabulary to hear what is being said quickly. It is important to point out that there are lots of websites or digital channels where the students and teacher can find TED Talks English video which provides speeches or presentations from world inspirational figures from various fields with various interesting topics. These video-based language learning make the students understand the influential TED Talks concepts and explore them more. Teaching English with TED Talks supports every English language program with easy-to-use classroom tools. TED talks are also great resources for teachers like approach to teaching ESL. English Language Teaching by using TED Talks is one of the authentic supplemental resources for English teachers to manage in English language learning programs.